1990
DOI: 10.1007/bf01233098
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese hamster V79 cell mutant V-H4 is phenotypically like Fanconi anemia cells

Abstract: It has been shown by genetic complementation analysis that a mitomycin C-sensitive mutant (V-H4) of Chinese hamster V79 cells is the first rodent equivalent of Fanconi anemia (FA) group A. The V-H4 mutant shows many typical characteristics of cells derived from FA patients. V-H4 cells exhibit increased sensitivity towards cross-linking agents as MMC (approximately 30-fold), cis-DDP (approximately 10-fold), DEB (approximately 10-fold), and PUVA (approximately 1.6-fold), but an only slightly increased sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The only exception was the cell line V-H4. V-H4 and FA-A may represent the same molecular defect since there is evidence from cell fusion studies to indicate that FA-A and V-H4 cell lines belong to the same complementation group (52). It is also possible that the V-H4 gene product participates in a step of the repair reaction subsequent to DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The only exception was the cell line V-H4. V-H4 and FA-A may represent the same molecular defect since there is evidence from cell fusion studies to indicate that FA-A and V-H4 cell lines belong to the same complementation group (52). It is also possible that the V-H4 gene product participates in a step of the repair reaction subsequent to DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…We only considered differences of more than twofold as biologically meaningful. Using these criteria, we found that two mutant Chinese hamster cell lines showed a twoto threefold decrease in the level of microhomologydirected end-joining, V-H4 and CL-V5B [36][37][38] (Table 2). To make this difference more easily visible, we also used another transfection reagent (Lipofectin instead of SuperFect), which results in a much higher relative level of microhomology use in wild-type cells (Table 3 and Fig.…”
Section: Mutants Showing Decreased Microhomology Usementioning
confidence: 99%
“…Genetic complementation analysis has shown that the Chinese hamster cell line V-H4, a mutant derived from the V79 cell line, belongs to the same complementation group as FA-A cells (Arwert et al, 1991). V-H4 cells are hypersensitive to many cross-linking agents such as MMC (30 fold more sensitive than the wild-type cells) (Zdzienicka et al, 1987) and exhibit an increased frequency of chromosomal breakage (Zdzienicka et al, 1990) and increased apoptosis (Papouli et al, 2000;Papouli et al, 2002) upon treatment with MMC. Since we previously demonstrated that V-H4 cells are not defective in the initial excision step of ICL repair (Larminat et al, 1998), this prompted us to study the efficiency of HR pathways in these cells.…”
Section: Introductionmentioning
confidence: 99%